2022
DOI: 10.1186/s12884-022-04884-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal safety outcomes after SAR-CoV-2 vaccination during pregnancy: a systematic review and meta-analysis

Abstract: Background and objective More than five million individuals died because of problems connected to COVID-19. SARS-Cov-2 poses a particular challenge to expectant mothers, who comprise one of the most vulnerable segments of the population. Our aim is to demonstrate the maternal and neonatal safety of the COVID-19 vaccine during pregnancy. Methods We searched PubMed, Cochrane Library, Scopus, Web of Science (WOS), Embase, Ovid, MedRxiv, and BioRxiv da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
1
8
0
4
Order By: Relevance
“…No theoretical or actual adverse effects have been prompted ( 21 23 ). No detrimental effects were observed among women who got vaccinated during pregnancy ( 18 20 ). Two recent cohorts among infertile couple in China also revealed that vaccination before ovarian stimulation had no effects on IVF outcomes ( 18 20 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No theoretical or actual adverse effects have been prompted ( 21 23 ). No detrimental effects were observed among women who got vaccinated during pregnancy ( 18 20 ). Two recent cohorts among infertile couple in China also revealed that vaccination before ovarian stimulation had no effects on IVF outcomes ( 18 20 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…No detrimental effects were observed among women who got vaccinated during pregnancy ( 18 20 ). Two recent cohorts among infertile couple in China also revealed that vaccination before ovarian stimulation had no effects on IVF outcomes ( 18 20 , 27 , 28 ). Thus, we recommended that clinicians could be more positive and encourage infertile couples with no other contradiction to take the vaccines as early as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varios estudios (15,16,17,18) concuerdan con la existencia de factores adversos, pero en menor medida, refieren que los más frecuentes son dolor en el lugar de la inyección, fiebre, malestar general, artralgia, dolor de cabeza, que fueron más comunes luego de la segunda vacunación.…”
Section: Discussionunclassified
“…Hagrass y col. (17) 2022 Resultados de seguridad materna y neonatal después de la vacunación SAR-CoV-2 durante el embarazo: una revisión sistemática y metaanálisis.…”
Section: Muestras De 39 Mujeres Embarazadasunclassified